A longitudinal reliability study of a consumer disidentification model - Prince, M.; Kwak, L. (Journal of Empirical Generalisations in Marketing Science, 2022)
Josiassen (2011) in a single cross-sectional survey investigated causal relations between consumer disidentification and domestic product judgments. The primary purpose of this replication paper is to evaluate the reliabilities of construct levels, as well as the significance, direction and magnitude of causal effects advanced in the original published structural model. The study measures relations between consumer disidentification (CDI) and domestic product judgments of American products over an extended 16 months period among second generation immigrants. In the present research the original CDI model fit was found to be longitudinally consistent and stable. Serendipitously, findings of the present study disclosed that over time baseline levels of consumer disidentification vary and actually declined significantly. Additionally, the negative effect of consumer disidentification on American product judgments significantly weakened over the course of the study. As an additional test of consumer predisposition reliability over time, the model in this study incorporated consumer xenocentrism (XEN) as a second predictor variable of domestic product judgments. Findings of this analysis were consistent with those found for CDI. These new phenomena have important theoretical and managerial implications. © 2022, University of South Australia. All rights reserved.
tex.author_keywords: Consumer disidentification; Ethnic identity and acculturation; Xenocentrism tex.document_type: Article tex.source: Scopus
Keywords: dept.mkt; peer-reviewed; ⛔ No DOI found